Screening and application of fungal proteases for goat casein hydrolysis towards the development of bioactive hydrolysates - Gomes, José Erick Galindo [UNESP] (2022)
Five protease-producing and non-mycotoxin-producing fungi (Mucor subtilissimus URM 4133, Mucor sp. URM 4146, Mucor guilliermondii URM 5848, Aspergillus viride-nutans URM 6629 and Penicillium decumbens URM 6018) were used for hydrolysis of caprine casein. Peptides obtained from different fungi were separated on two fractions: molecular mass (MM) < 3 kDa and MM from 3 to 10 kDa, and the peptide fractions were investigated for antimicrobial, antioxidant and antihypertensive bioactive properties. All the 3 to 10 kDa fractions of all fungi were able to inhibit the growth of the three Gram-negative bacteria and the hydrolysate from URM 5848 inhibited all bacteria, except the bacteria Gram-positive Enterococcus faecalis. All hydrolysates with the peptides between 3 and 10 kDa possessed a strong scavenging capacity for ABTS•+ [2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid)] and DPPH (2,2-diphenyl-1-picrylhydrazyl) radicals, in which URM 5848 (100% and 32%) and URM 4133 (99% and 29%), respectively for (ABTS•+ and DPPH) were the best hydrolysates. The antihypertensive activity was only observed for hydrolysates from the URM 5848 and URM 4133 fungi, and the higher inhibitory effect was observed on fractions < 3 kDa with URM 5848, 19% and URM 4133, 16%. This work was successful in demonstrating the hydrolysates from goat casein by selected fungal proteases are effective in producing different bioactive peptides.